Development of new wine‐, dried‐ and tablegrape scions and rootstocks for Australian viticulture: past, present and future. (9th March 2022) - Dry, I.B.; Davies, C.; Dunlevy, J.D.; Smith, H.M.; Thomas, M.R.; Walker, A.R.; Walker, R.R.; Clingeleffer, P.R.
Abstract: This review highlights the contributions of CSIRO to the development of new scions and rootstocks for the Australian winegrape, driedgrape and tablegrape industries. Initially, CSIRO played a pivotal role in the selection of high‐yielding Sultana clones which contributed over half the total Australian grape crop in the 1970s used for wine‐ and driedgrape production. It was also responsible for importation and evaluation of the Salt Creek (syn. Ramsey) rootstock which provided tolerance to root‐knot nematodes and salinity and became the most widely adopted rootstock for the emerging Australian wine industry in the 1980–1990s. The CSIRO has also successfully bred or released several new grape cultivars. While the adoption rate for the CSIRO wine cultivars has been limited, CSIRO‐selected cultivars dominate the Australian driedgrape industry, while CSIRO‐released cultivars continue to play an important role in the Australian tablegrape industry. In the 1990s, CSIRO commenced the application of molecular biology techniques for grapevine germplasm improvement. Researchers from CSIRO were some of the first in the world to successfully regenerate transgenic grapevines and demonstrate the potential of this technology to produce low‐browning driedgrapes and mildew‐resistant premium winegrapes. More recently, the focus has shifted to the mapping of resistance loci from wild grape species and their introgression into new winegrape scions to provide resistance to mildews and new rootstocks to provide durable resistance to rootknot nematodes and phylloxera. Finally, this review considers some future challenges faced by the Australian grape industries and how these might be addressed using conventional or molecular breeding strategies.